Apply the Associative and Commutative Properties to generate an expression equivalent to 2(a+5)+4(2a+3)−10 .(1 point)

Responses

10a +12
10 A plus 12

10a +22
10 A plus 22

12a+10
12 A plus 10

9a +12

1 answer

To apply the Associative Property, we can group like terms together:

2(a + 5) + 4(2a + 3) - 10
= 2a + 10 + 8a + 12 - 10
= (2a + 8a) + (10 + 12) - 10
= 10a + 22 - 10

Now, let's apply the Commutative Property to rearrange the terms:

10a + 22 - 10
= 10a - 10 + 22
= 10a + 12

Therefore, the expression equivalent to 2(a + 5) + 4(2a + 3) - 10 is 10a + 12.